The missional church and denominations : helping congregations develop a missional identity - Van Gelder, Craig (Grand Rapids, MI : William B. Eerdmans Pub., 2008)
"The Missional Church and Denominations utilizes the missional church conversation as a lens for engaging an important dimension of church life in the United States - denominations and denominationalism." "Denominations have been studied from a wide variety of perspectives, including historical, sociological, and theological, but they have yet to be engaged in light of a missional church understanding. Here each essay helps to bring further clarity to the word "missional" and contributes to the ever-widening conversation."--BOOK JACKET.
Introduction: Engaging the missional church conversation -- A missional engagement with denominations and denominationalism -- An ecclesiastical geno-project : unpacking the DNA of denominations and denominationalism / Craig Van Gelder -- Living in the city, journeying outside the gate : a missional approach to polity / David G. Forney -- Reframing denominations from a missional perspective / Alan J. Roxburgh -- The challenge of developing missional denominational agencies and the implications for leadership / Marion Wyvetta Bullock -- A missional reframing of ecclesiology and polity for specific denominations -- A more true "domestic and foreign missionary society" : toward a missional polity for the Episcopal Church / Dwight Zscheile -- Missional DNA of the Evangelical Lutheran Church in America / Daniel R. Anderson -- Missional ordered ministry in the Evangelical Covenant Church : moving toward apostolic imagination / Kyle J.A. Small -- Missional renewal : an ecclesiology and polity proposal for the Baptist General Conference / Todd Hobart -- Epilogue: The story of one denomination seeking to become missional -- Insights into becoming a missional denomination : the Reformed Church in America / Wesley Granberg-Michaelson.
Includes bibliographical references.
Keywords: Mission of the church; Church; Missions -- Theory; Christian sects